Effectiveness of SARA reform in sub-Saharan Africa - (:unkn) unknown (My University, 2021)
This paper identifies impact of semi-autonomous revenue authorities in sub-Saharan Africa tax revenues. Results show that reform of semi-autonomous revenue authorities got various effects on tax revenues in short term. However, in medium term, semi-autonomous revenue authorities didn't work better than traditional tax administration. These results leads to conclude that sub-Saharan African countries which have not yet adopted the SARA reform, can increase their tax effort and thus their level of taxation by improving quality of institutions and by modernizing traditional administrations.
Keywords: African Research